Research on goats: Opportunities and challenges - Devendra, C. (Institut National de la Recherche Agronomique, 2000)
The paper emphasises the potential opportunities and challenges to improve productivity in goats and improve the livelihoods of the poor. An assessment of research activities confirms the continuing trend about emphasis on basic research and along disciplinary lines. The importance of shifting research programmes to give more emphasis to applied and adaptive efforts that respond to needs on-farm, based on constraint analyses are emphasised, in which a systems approach and holistic focus is necessary. The justification for ensuring relevance and demonstrable impact is dictated by diminishing interest and research budgets and donor support.